1992
DOI: 10.1002/em.2850200410
|View full text |Cite
|
Sign up to set email alerts
|

DNA adduct formation in mice following dermal application of smoke condensates from cigarettes that burn or heat tobacco

Abstract: A prototype cigarette that heats tobacco (test cigarette), developed by R.J. Reynolds Tobacco Company, has yielded consistently negative results in several in vivo and in vitro genetic toxicology tests. The objective of the present study was to evaluate the potential of cigarette smoke condensate (CSC) from the test cigarette to induce DNA adducts in mouse tissues and compare the results with those obtained with CSC from a reference tobacco-burning cigarette (1R4F). CD-1 mice were skin-painted with CSC from re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Mutants at Thr-321 (T321S, T321P) varied in activity, with less efficiency in some cases but more in others (Figure 3B). Shimizu also reported that the rat P450 1A2 T319A mutant had low activity in some reactions but elevated activity in others (28,31,32). These shifts in activity were typically accompanied by increases in the respective K m .…”
Section: Discussionmentioning
confidence: 91%
“…Mutants at Thr-321 (T321S, T321P) varied in activity, with less efficiency in some cases but more in others (Figure 3B). Shimizu also reported that the rat P450 1A2 T319A mutant had low activity in some reactions but elevated activity in others (28,31,32). These shifts in activity were typically accompanied by increases in the respective K m .…”
Section: Discussionmentioning
confidence: 91%